KOMPOSISI SPESIES TERIPANG (Holothuroidea) DI PERAIRAN KAMPUNG KAPISAWAR DISTRIK MEOS MANSWAR KABUPATEN RAJA AMPAT - Tutik Handayani; Vera Sabariah; Ronald R. Hambuako (Jurnal Perikanan Universitas Gadjah Mada, 2017)
This study aimed to investigate the species and its composition of sea cucumber in the Kapisawar village of Meos Manswar District in Raja Ampat Regency. This research was conducted from March to April 2014. Descriptive method was applied directly through observations by using belt transects that consisted of three stations. Then, identification of species was done through spicula appearance of sea cucumbers. Results showed that from all research stations, 10 species of sea cucumbers were found, and these species derived from 3 families and 4 genera. The species of sea cucumbers are Holothuria scabra, H. leucospilota, H. rigida, H. sucosa, Bohadschia similis, B. marmorata, B. vitiensis, Synapta maculate, Opheodesoma grisea and Stichopus variegatus. The highest number of sea cucumber species was found in the station I which consisted of 9 species from 2 families and 4 genera, followed by station II (2 families and 3 genera), and the lowest at the station III of 3 species (2 families and 2 genera). Some of the sea cucumber found in the research station were economic importance, with the highest composition was at the station I because of its suitable habitat condition and the lowest in station III due to far from the village.